Clinical Features and Drug Characteristics of Patients with Generalized Fixed Drug Eruption in the West of Iran (2005–2014). (10th December 2015) - Kavoussi, Hossein; Rezaei, Mansour; Derakhshandeh, Katayoun; Moradi, Alireza; Ebrahimi, Ali; Rashidian, Harif; Kavoussi, Reza
Abstract : Background. Generalized fixed drug eruption is a specific variant of fixed drug eruption with multifocal lesions. Diagnosis of this drug reaction is straightforward, but occasionally recognition of the causative drug is not possible. This study was aimed at evaluating the clinical features and culprit drugs in generalized fixed drug eruptions in the west of Iran. Method. This cross-sectional study was carried out on 30 patients with criteria of generalized fixed drug eruption over 9 years. Demographic, clinical, and drug intake information were collected. Results. Out of 30 patients (17 females and 13 males) with the mean age of26.67 ± 10.21 years, 28 (93.3%) and 2 (6.7%) cases had plaque and bullous clinical presentation, respectively. Upper limbs were the most common (90%) site of involvement. The antibiotic group, especially cotrimoxazole (26.1%), was reported to be the most common offending drug, but the causative drug was not determined in 7 (23.3%) patients. Conclusion. Many cases of generalized fixed drug eruption firstly presented as limited lesions and led to generalized lesion due to repeated intake of the causative drug. No causative drug was found in some patients, which might be associated with concurrent intake of several drugs, multiple FDE, and peculiarity of the patch test.